Effect of crosslinking with Ca++ and Zn++ in the formation of gellan gum gels - Verma A.; Wahi A.K.; Pandit J.K. (My University, 2025)
This study involves an investigation of the effects of crosslinking of gellan gum (GG) with Ca++ or Zn++ on the physical properties of GG gels. GG gels crosslinked with different concentrationsdifferent concentrations of Ca++ or Zn++ were prepared and parameters such as % water holding capacity and penetration thickness were investigated as measures of the extent of interaction of Ca++ or Zn++ with GG molecules. Data generated from the above studies revealed that Zn++ interacted with the GG molecules to a greater extent than Ca++. In order to further strengthen our finding, we have prepared Zn++ crosslinked and Ca++ crosslinked floating GG beads respectively by ionotropic gelation in the presence of a gas-generating agent (NaHCO3) and compared their physico-chemical properties such as density, drug entrapment efficiency and release in 0.1 M HCl (pH 1.2) using metronidazole (MTZ) as a model drug. Experimental data suggested that Zn++ crosslinked floating GG beads were denser and less buoyant than Ca++ crosslinked floating beads but capable of significantly (p < 0.05) improving MTZ entrapment efficiency and sustaining the MTZ release in 0.1 M HCl (pH 1.2) compared to Ca++ crosslinked floating beads. The difference in observed behavior may be attributed to differences in specificity, soft and hard character, enthalpies of hydration and ionization potentials of Ca++ and Zn++.